2004
DOI: 10.2116/analsci.20.1347
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Scattering from Oleate-Stabilized Silver Colloids at a Liquid/Liquid Interface

Abstract: Oleate-stabilized silver colloids of 5-nm-diameter were adsorbed to a toluene/water interface, and surface enhanced Raman scattering (SERS) spectra from these colloids were measured under the total internal reflection (TIR) condition. From the observed spectra, we examined the states of oleate ions and toluene molecules on silver colloids at the liquid/liquid interfacial region. The TIR-SERS spectra of oleate ions showed stronger peaks of the carboxylate group and the ethylene group than those of alkyl chains.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 33 publications
(39 reference statements)
1
39
0
Order By: Relevance
“…Although the observed peak position of the surface plasmon band is slightly larger than these previously reported, its position is still consistent with Mie theory predictions. This optical absorption strongly depends on particle size, extent of aggregation, 32 dielectric, and chemical properties of the milieu. 33 Small silver spherical nanoparticles (i.e., <20nm diameter) exhibit a single, narrow surface plasmon band inconsistent with experimental observations here.…”
Section: Resultsmentioning
confidence: 99%
“…Although the observed peak position of the surface plasmon band is slightly larger than these previously reported, its position is still consistent with Mie theory predictions. This optical absorption strongly depends on particle size, extent of aggregation, 32 dielectric, and chemical properties of the milieu. 33 Small silver spherical nanoparticles (i.e., <20nm diameter) exhibit a single, narrow surface plasmon band inconsistent with experimental observations here.…”
Section: Resultsmentioning
confidence: 99%
“…This resulted in the ligands in the aqueous phase arranging with the charged head group pointing into the solution and on the organic side the head group is involved in bonding with the nanoparticle surface while the non-charged alkyl tail group points into the solution ( Figure 14). 129 When thiophene was used as the organic phase solution it was observed that the organic solvent was able to replacing some of the citrate particles adsorbed on the surface of the nanoparticles held at the interface resulting in the formation of a Janus particle structure. 45 These observations suggest that the assembly at the liquid/liquid interface may have a substantial influence on the ligand structure on the surface, indicating that some alteration of the surface chemistry may occur, driven by the reduction in surface energy.…”
Section: Surface Enhanced Raman Scattering (Sers)mentioning
confidence: 99%
“…UV-vis spectra give considerable information about the growth and shape-size accord of nanoparticles. It is pertinent to mention that the Plasmon peak and the full-width of half-maximum (fwhm) depend on the extent of colloid aggregation (Yamamoto, Fujiwara, & Watari, 2004). Colloidal aggregation resulting in larger particle size often leads to red shift in the spectrum.…”
Section: Preparation and Characterization Of The Starch Supported 'Grmentioning
confidence: 99%